Maxim of Approbation in Pride and Prejudice: A Pragmatic Study of Praise Strategies - Ridha, Nikmatul; Putri, Gita Indriani; Bobihu, Anisa Fazrun; Nurjannah, Anggun (Lembaga Publikasi Ilmiah Dwipantara, 2025)
This study investigates the use of the Approbation Maxim in Jane Austen’s Pride and Prejudice through a pragmatic lens, focusing on how compliments function within character interactions. Drawing on Leech’s (1983) Politeness Principle, particularly the maxim of Approbation, the research explores praise as a linguistic strategy for managing face, expressing transformation, and navigating social hierarchies. Using a qualitative descriptive method and discourse analysis, 27 utterances were identified and categorized by topic—appearance, ability, and personality. The findings reveal that praise in the novel is shaped by gender roles, social class, and interpersonal motives, functioning not merely as politeness but also as a tool for emotional and relational negotiation. Characters such as Mr. Darcy and Elizabeth Bennet exhibit varying degrees of sincerity and strategic politeness, reflecting broader cultural values embedded in 19th-century English society. The study affirms the relevance of pragmatic theory in literary analysis and offers insights for further interdisciplinary exploration.